Blackout - Willis, Connie (Spectra Ballantine Books, 2010)
When a time-travel lab suddenly cancels assignments for no apparent reason and switches around everyone's schedules, time-traveling historians Michael, Merope, and Polly find themselves in World War II, facing air raids, blackouts, unexploded bombs, dive-bombing Stukas, rationing, shrapnel, V-1s, and two of the most incorrigible children in all of history--to say nothing of a growing feeling that not only their assignments but the war and history itself are spiraling out of control.